2011
DOI: 10.1111/j.1365-2982.2011.01809.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gastric acid on gastric emptying and gastric distension‐induced pain response in rats – effects of famotidine and mosapride

Abstract: We established rat models to evaluate the effect of gastric acid hypersecretion on gastric emptying and the GD-induced pain response. In these models, acid hypersecretion delayed gastric emptying and aggravated the pain response. Furthermore, we showed that famotidine ameliorated both delayed gastric emptying and gastric hypersensitivity, whereas mosapride only improved delayed gastric emptying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…The T 50 values in rats and dogs are consistent with those reported for humans (8–25 min range) . Although several studies have demonstrated that pentagastrin delays the gastric emptying in rats and dogs, we observed no significant changes in the GET in this study. This discrepancy may be explained by the differences in dosage and administration route, as gastric emptying was significantly delayed by the intraperitoneal administration of pentagastrin at a high dose, in a preliminary study using rats (data not shown).…”
Section: Discussionsupporting
confidence: 90%
“…The T 50 values in rats and dogs are consistent with those reported for humans (8–25 min range) . Although several studies have demonstrated that pentagastrin delays the gastric emptying in rats and dogs, we observed no significant changes in the GET in this study. This discrepancy may be explained by the differences in dosage and administration route, as gastric emptying was significantly delayed by the intraperitoneal administration of pentagastrin at a high dose, in a preliminary study using rats (data not shown).…”
Section: Discussionsupporting
confidence: 90%
“…Mosapride is available as a prokinetic agent in many Asian countries. Preclinical and clinical studies provided evidence for mosapride as a useful therapy for FD by showing its stimulating effect on gastric emptying, gastric accommodation and gastric motility in rats and healthy subjects . Thus far, no mechanistic studies in FD patients have been performed.…”
Section: Current Treatment Options For Functional Dyspepsiamentioning
confidence: 99%
“…In that study, while pentagastrin-induced gastric acid hyper-secretion aggravated the pain response to gastric dilation by delaying gastric emptying, the histamine H2 blocker famotidine, but not the prokinetic drug mosapride, successfully ameliorated the pain response. 33 Several limitations associated with the present study warrant mention. First, regarding the illness period, we defined dyspeptic symptoms lasting for more than 1 month as FD.…”
Section: Discussionmentioning
confidence: 88%